A Novel Immune-Related Three-Gene Signature and Immune Infiltration Insights in Psoriasis and Chronic Kidney Disease - Yin T; Zhang T; Ma L (Clinical, Cosmetic and Investigational Dermatology)
Tingting Yin, Tingting Zhang, Lei Ma College of Life Science, Shihezi University, Shihezi, Xinjiang, People’s Republic of ChinaCorrespondence: Tingting Zhang; Lei Ma, Email zting@shzu.edu.cn; malei1979@hotmail.comPurpose: There are significant inflammatory correlations and common immune dysregulation features between psoriasis and chronic kidney disease, however, the inflammatory mechanisms of these two diseases have not been clarified. The aim of this study was to screen immunologically related biomarkers for psoriasis and chronic kidney disease with the objective of identifying specific molecular markers to improve the accuracy and sensitivity of disease diagnosis.Patients and Methods: To achieve this objective, common differentially expressed genes between psoriasis and chronic kidney disease were first identified. Through further functional analysis, these genes were found to be primarily involved in the activation of inflammation and innate immune responses. Subsequently, six hub genes were determined using five topological algorithms. The responses of these two diseases exhibited similar changes in immune reactions. By cross-analyzing these key genes with known immune genes, three Immunity-Related Hub Genes (IRHGs) were identified, including MX1, DDX58, and ISG20.Results: ROC curve analysis validated the excellent discriminative ability of MX1 and ISG20 in both diseases. Furthermore, immune infiltration analysis revealed a higher abundance of T cells in samples from both psoriasis and chronic kidney disease, suggesting that T cell-driven immune responses may play a crucial role in the association of these two diseases. Lastly, single-cell analysis observed a significant increase in the cell abundance of T cells and endothelial cells in psoriasis and chronic kidney disease, respectively. The differential expression of MX1, DDX58, and ISG20 in these cells suggests that they may be involved to varying degrees in the pathogenic mechanisms of the two diseases.Conclusion: This study provides a theoretical foundation for prognosis assessment and treatment of psoriasis and chronic kidney disease, contributing to a deeper understanding of the immune mechanisms underlying these conditions.Keywords: psoriasis, chronic kidney disease, WGCNA, immune infiltration, single cells